Customer knowledge about purchasing perceptions, safety and quality issues of Syrian cheese in Egypt - Tarabiya, Omar F.; Awaad, Shimaa S.; Sallam, Said S.; Abdel-Salam, Ayah B. (Journal of Advanced Veterinary Research, 2024)
Food safety is a crucial global public health issue. Food-borne diseases are mostly due to lack of knowledge about food processing, storage, and handling practices. Consumer’s behavior towards food safety should be considered during implementation of control measures to eliminate potential hazards and keep the products quality. Syrian cheeses such as Akawi, Halloumi, and Mudaffara are nowadays commonly produced and sold in Egyptian markets, with high acceptability from the Egyptian consumer’s side. The present cross-sectional study was designed using a structural questionnaire to estimate the consumer familiarity and consumption rates of such products. Meanwhile, evaluating the consumers Knowledge, attitude, and practices (KAP) among Syrian cheeses safety, quality, purchasing and storage parameters. The study was conducted online by 407 Egyptian citizens from different districts in Greater Cairo governorates. The questionnaire included thirty questions divided into 4 sections: sociodemographic questions; Syrian cheese general consumption data base; the consumer’s Attitude and Practice; and the knowledge level toward the products. Most of the responders were females (66%), with age range 20-40 years (76%), university graduates (64%) and work in public health field (57%). 51% of the responders consume Syrian cheese, while 70% prefer the Egyptian cheese. 47.8% used to consume Syrian cheese indirectly in food recipes. About 31% of the Egyptian consumers often considered Syrian cheese as a high-quality product and 64.2% select the products on flavor basis. Only 5% of the responders suffered after Syrian cheese consumption and 3% have allergy from cheeses. Regarding safety and quality of Syrian cheeses, 47% of the responders have good knowledge about the necessity of cold storage of cheese. Although the shelf life of soft cheese is one month, however only 8% knew that, and 67.5% used to keep Syrian cheese in refrigerator till consumption regardless to the shelf life. 64.4% of responders accepted the addition of chemical preservatives to cheese but within the acceptable limits, and at the same time 92% preferred the natural ones. Most of responders have a good knowledge level about: the incidence of food poisoning from cheese (77.3%), food poisoning symptoms (87.8%), and the main causative agent of such cases (53%).